Preemptive Living-Related Kidney Transplantation Is a Cost-Saving Strategy Compared With Post-dialysis Kidney Transplantation in Thailand - Phongphithakchai, Atthaphong; Phisalprapa, Pochamana; Kositamongkol, Chayanis; Premasathian, Nalinee; Larpparisuth, Nuttasith; Skulratanasak, Peenida; Vongwiwatana, Attapong (Frontiers in Medicine, 2022)
Background: Compared with other kidney replacement therapies, preemptive kidney transplantation (KT) provides better clinical outcomes, reduces mortality, and improves the quality of life of patients with end-stage kidney disease (ESKD). However, evidence related to the cost-effectiveness of preemptive living-related KT (LRKT) is limited, especially in low- and middle-income countries, such as Thailand. This study compared the cost-effectiveness of LRKT with those of non-preemptive KT strategies. Methods: Cost and clinical data were obtained from adult patients who underwent KT at Siriraj Hospital, Mahidol University, Thailand. A decision tree and Markov model were used to evaluate and compare the lifetime costs and health-related outcomes of LRKT with those of 2 KT strategies: non-preemptive LRKT and non-preemptive deceased donor KT (DDKT). The model’s input parameters were sourced from the hospital’s database and a systematic review. The primary outcome was incremental cost-effectiveness ratios (ICERs). Costs are reported in 2020 United States dollars (USD). One-way and probabilistic sensitivity analyses were performed. Results: Of 140 enrolled KT patients, 40 were preemptive LRKT recipients, 50 were non-preemptive LRKT recipients, and the rest were DDKT recipients. There were no significant differences in the baseline demographic data, complications, or rejection rates of the 3 groups of patients. The average costs per life year gained were $10 647 (preemptive LRKT), $11 708 (non-preemptive LRKT), and $11 486 (DDKT). The QALY gained of the preemptive option was 0.47 compared with the non-preemptive strategies. Preemptive LRKT was the best-buy strategy. The sensitivity analyses indicated that the model was robust. Within all varied ranges of parameters, preemptive LRKT remained cost-saving. The probability of preemptive LRKT being cost-saving was 79.4%. Compared with non-preemptive DDKT, non-preemptive LRKT was not cost-effective at the current Thai willingness-to-pay threshold of $5113/QALY gained. Conclusions: Preemptive LRKT is a cost-saving strategy compared with non-preemptive KT strategies. Our findings should be considered during evidence-based policy development to promote preemptive LRKT among adults with ESKD in Thailand.